Prenatal Human Immunodeficiency Virus Testing and Patient Management by Obstetricians in a High Seroprevalence Community - William R. Robinson; Michael Fleischer (Hindawi Limited, 1994)
Objective: In order to determine the practice habits of obstetricians concerning frequency of prenatal human immunodeficiency virus (HIV) testing and management strategies for HIV-seropositive obstetric patients, we conducted a telephone survey of practicing obstetricians over a 3-month period.